Infectious Diseases : A Treatise of Infectious Processes - HOEPRICH, Paul D; JORDAN, M.Colin; RONALD, Allan R (J.B.Lippincott Comp, 1994)
The fifth edition of this classic text continues to deliver an up-to-date synthesis of information relevant to the understanding, diagnosis, management and prevention of infectious diseases. This edition boasts the addition of a new editor, 64 new contributors, an expanded color section and 11 new chapters. A sampling of the new material covered includes: Infections Caused by Haemophilus Influenza, Erythema Infectiosum (Parvovirus B-19 Infection), Human T-Cell Leukemia Virus, Ehrlichiosis, Pyomyositis and Landry-Guillain-Barre Syndrome.
Keywords: infekční nemoci; INFEKČNÍ NEMOCI; infektologie